MODEL KOMUNIKASI ANTAR BUDAYA KELUARGA MIXED MARRIAGE DI WILAYAH BUDAPEST-HUNGARIA - Zikri Fachrul Nurhadi; Heri Hendrawan; Desyya Fira Ayutria (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2019)
This study aims to discover the motives, experiences, meaning, and intercultural communication of mixed marriage couples in the Budapest-Hungary. The research uses phenomenology method Alfred Schutz and Husserl to examine the experience of people. Data are collected through observation, interviews through social media and literature study. The subjects are six mixed marriage couple living in Budapest-Hungary using purposive sampling technique. This research found a model of intercultural communication among mixed marriage couples related to motives, experiences, meanings, and intercultural communication based on cultural differences, languages, mindsets, as well as stereotypes of certain religions in which mixed marriage couples can adapt to the situation. This study contributes to four communication models of mixed marriage couples, namely motives, experiences, meanings and intercultural communication.